2018
DOI: 10.5114/hm.2018.83386
|View full text |Cite
|
Sign up to set email alerts
|

Space configuration and numerical relationship during professional soccer matches: a proposal for small-sided games design

Abstract: Purpose. the purpose of this study was to analyse the most recurrent characteristics of soccer attacking sequences regarding the effective space available, the numerical relationship, and the distance between the defensive line and the goal. Methods. Overall, 4 Brazilian professional matches were recorded and the trajectories of 101 players were obtained by a tracking method. the variables of the studies were: length (the distance between 2 more distant players, longitudinally), width (the distance between 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Based on the above review, in fact many previous researchers have revealed the performance of soccer at the elite or professional level namely, the playing style of a team when attacking and defending was analyzed [14], physical and technical performance in each different playing position in the English Premier League [15], identification of scoring opportunities and offensive and defensive strategies as indicators that can be distinguished between teams winning or losing matches in the 2012 European Soccer Championship [16], percentage of ball possession and successful passing of teams that were successful in 2014 FIFA World Cup [17], technical performance profiles of the teams involved in the 2016 European Soccer Championship [3], described how scoring opportunities arise and chances were executed in Major League Soccer by considering indicators of offensive and defensive tactics [18], measuring guard performance goal in all matches at EURO 2016 [19], the level of centrality between playing positions in the national team that played in the 2014 FIFA World Cup [20], analysis of goalkeeper performance related to the role in the game [21], competitive profile of the best leagues in Europe such as the Spanish League, Italian League, English League, Germany League, Portuguese and French Leagues [22], the characteristics of the sequence of attacks in soccer that are most effective on the opponent's defensive area, and the distance between the defensive line and the goal [23], the situation of the game from the recovery of the ball to the goals scored by professional soccer players. men's and women's League 1 Portugal [24], identification of technical and tactical action at each player position during play in the Ukraina Premier League [25], characteristics of goal scoring passing networks during the 2016 European Soccer Championships [26], influence of small-sided games on the game performance of young soccer players [27], observation of the motor activities of Greece professional soccer players on this during one competitive season [28], analysis of the quality of the team in the ball recovery which is influenced by the quality of the opponent, the quality of the field and the status of the match [7], shooting characteristics and goal scoring in the 2019 Women World Cup Soccer Tournament [29], analysis of the goal process scored during Euro 2020 [30], and analysis of corner kicks during the 2018 FIFA World Cup [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above review, in fact many previous researchers have revealed the performance of soccer at the elite or professional level namely, the playing style of a team when attacking and defending was analyzed [14], physical and technical performance in each different playing position in the English Premier League [15], identification of scoring opportunities and offensive and defensive strategies as indicators that can be distinguished between teams winning or losing matches in the 2012 European Soccer Championship [16], percentage of ball possession and successful passing of teams that were successful in 2014 FIFA World Cup [17], technical performance profiles of the teams involved in the 2016 European Soccer Championship [3], described how scoring opportunities arise and chances were executed in Major League Soccer by considering indicators of offensive and defensive tactics [18], measuring guard performance goal in all matches at EURO 2016 [19], the level of centrality between playing positions in the national team that played in the 2014 FIFA World Cup [20], analysis of goalkeeper performance related to the role in the game [21], competitive profile of the best leagues in Europe such as the Spanish League, Italian League, English League, Germany League, Portuguese and French Leagues [22], the characteristics of the sequence of attacks in soccer that are most effective on the opponent's defensive area, and the distance between the defensive line and the goal [23], the situation of the game from the recovery of the ball to the goals scored by professional soccer players. men's and women's League 1 Portugal [24], identification of technical and tactical action at each player position during play in the Ukraina Premier League [25], characteristics of goal scoring passing networks during the 2016 European Soccer Championships [26], influence of small-sided games on the game performance of young soccer players [27], observation of the motor activities of Greece professional soccer players on this during one competitive season [28], analysis of the quality of the team in the ball recovery which is influenced by the quality of the opponent, the quality of the field and the status of the match [7], shooting characteristics and goal scoring in the 2019 Women World Cup Soccer Tournament [29], analysis of the goal process scored during Euro 2020 [30], and analysis of corner kicks during the 2018 FIFA World Cup [5].…”
Section: Introductionmentioning
confidence: 99%